Cueing God: Religious Cues and Voter Support. Issue 2 (13th February 2014) - McLaughlin, Bryan; Wise, David
Abstract Scholars contend that correctly applying religious cues is crucial to winning political elections. This article examines the effect of general religious cues by conducting an experiment on a national sample (N = 520). Through the use of a fictitious congressional candidate's webpage, we examine how subtle and overt religious cues interact with citizen religiosity to affect political evaluations. The findings demonstrate that politicians who use overt religious cues run the risk of alienating a large portion of potential voters. Religious cues do, however, appear to become more effective as citizens become more religious. We also find some evidence that overt religious cues are more polarizing than subtle religious cues. This article provides a foundation from which to more thoroughly consider how general religious cues can affect political outcomes and how these cues may interact with other factors.